Comparative effectiveness of immediate antiretroviral therapy versus CD4-based initiation in HIV-positive individuals in high-income countries: observational cohort study. - Lodi, Sara; Phillips, Andrew; Logan, Roger; Olson, Ashley; Costagliola, Dominique; Abgrall, Sophie; van Sighem, Ard; Reiss, Peter; Miró, José M; Ferrer, Elena; Justice, Amy; Gandhi, Neel; et al. (The lancet. HIV, 2015)
Recommendations have differed nationally and internationally with respect to the best time to start antiretroviral therapy (ART). We compared effectiveness of three strategies for initiation of ART in high-income countries for HIV-positive individuals who do not have AIDS: immediate initiation, initiation at a CD4 count less than 500 cells per μL, and initiation at a CD4 count less than 350 cells per μL.